Asuhan Keperawatan Keluarga Tn.T Khususnya Ny.M Dengan Gangguan Sistem Persarafan: Stroke Non Hemoragik Di DesaJagalan Rt 01 Rw 07 Pabelan Kartasura Wilayah Kerja Puskesmas Kartasura - wicaksono, dody putut, H.M. Abi Muhlisin, SKM., M.Kep (2015)
Background: Strokenon hemorrhagic attack occurred at the age of 20-60 years and a rule arise after physical activity or due to psychological (mental), and due to the mechanisms of vascular embolism, thrombosis or hemodinamik.Purpose: to knowing nursing patients with non-hemorrhagic stroke that include assessment, intervention , implementation and evaluation of nursing. Methods: The method used is to make the process of nursing care in patients with non-hemorrhagic stroke Results: After doing during the 3x24-hour nursing care problems perfusi jaringan cerebral, physical gangguan mobilitas partially resolved and a lack of nutrients from the needs resolved. Conclusions: 1 diagnoses that have been resolved and there are two diagnoses or nursing problems were only resolved in part, namely for the diagnosis of ineffectiveness disorders of cerebral tissue perfusion associated with arterial disorders and diagnoses of physical mobility disorders associated with neuro muscular damage. Thus requiring further treatment. Keywords: Stroke, nerves, non-hemorrhagic, ischemic, infarction